In vitro anthelmintic activity of pineapple peel juice (Ananas comosus (L.) Merr.) against Paramphistomum sp. - Damiyati, Siska Yunita; Pratama, Iman Surya; Tresnani, Galuh (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2021)
Pineapple peel (Ananas comosus (L.) Merr.) has a potential natural-based anthelmintic agent. This study aimed to determine the effective concentration of pineapple peel juice against Paramphistomum sp. in vitro. Adults Paramphistomum sp. were divided into 5 test groups, the control group contained Albendazole 10% w/v, the nontreatment group contained NaCl 0.9% w/v and the treatment group contained pineapple peel juice with concentration of 12.5, 20, and 25% w/v. The number of live flukes and the motility scores were recorded every 15 minutes for 5 hours of incubation. The Survival Index (SI) and Relative Motility (RM) of flukes were calculated and statically analyzed using SPSS version 23 software. SI values of flukes in the 12.5, 20, and 25% w/v concentration of treatment group were 46.3, 50.0, and 38.9% respectively. RM values of flukes in the 12.5, 20 and 25% w/v concentration of treatment groups were 39.1, 42.0, and 34.1 respectively. RM values of flukes in the 12.5, 20 and 25% w/v concentration of treatment groups were 39.1359, 42.0249, and 34.1174 respectively. This research showed that, pineapple peel juice 25% w/v was effective against Paramphistomum sp. with survival index and relative motility values comparable to Albendazole 10% w/v (p <0.05).